Sympathetic Trip Analysis in Distribution System of PLTU and PLTA Nagan Raya - Muhammad Mizwar; Tarmizi Tarmizi; Ramzi Adriman (PTE FTK UIN Ar-Raniry, 2024)
At the PT unit, PLN (Persero), there is an issue with the 20 kV electric power distribution system, such as feeder disruption. As a result, many felt sorry for the feeders of PLTA Krueng Isep and PLTU Nagan Raya, whose consumers were without power for extended periods of time. Of course, it can impact how well a business performs, particularly in terms of service and electrical revenue. In order to examine the causes of Sympathetic, study is required. In order to conduct the research, data on disturbances are gathered, tests are run, simulation results are analyzed using the ETAP application, non-directional relays are swapped out for directional relays, protection coordination is reset, and evaluation is done. The findings of this study have the potential to improve performance at PT. PLN (Persero) and decrease or even completely eradicate the incidence of sympathy in the 20 kV distribution network.